cDNA Cloning of Stearoylacp Desaturase (sad) Gene from Palm Oil (Elaes guineensis) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
As one of the source of edible oil used in food, the quality of palm oil becomes an important parameter. Nowadays, consumers demand edible oil which is high in unsaturated fatty acid due to the link of saturated fatty acid with cholesterol. In order to overcome the slow process of breeding program due to the length of the life cycle of palm oil, transgenic palm oil with higher unsaturaed fatty acid is constructed. The first step to achieve this goal is cloning the target gene from the palm oil mesocarp using PCR method with cDNA as the template. In this experiment, cDNA was synthesized from total RNA isolated from palm oil mesocap and specific primer pairs was designed. At the end of this experment, a 541 by DNA fragment was obtained and proved by sequencing as a fragment of gene encoding Stearoyl ACP Desaturase (sad) from palm oil (Elaeis guineensis) mesocarp.